Targeting the poor in Mexico: an evaluation of the selection of households for PROGRESA - Skoufias, Emmanuel; de la Vega, Sergio; Davis, Benjamin (International Food Policy Research Institute, 2001)
This report reevaluates PROGRESA’s targeting methods since the program began adding beneficiary households through a process called “densification.” The authors first evaluate PROGRESA’s accuracy in targeting both at the community and household levels. Second, they evaluate the targeting in terms of its impact on poverty alleviation relative to other feasible methods assuming the same total budget.